Travel and Transcendence: Spiritual Awakening in Matthiessen’s The Snow Leopard (Prithvi Academic Journal, 2026)
This study explored spiritual awakening and sublime feeling in Peter Matthiessen’s novel The Snow Leopard. It chronicled a transformative journey through the Western Himalayas of Nepal, undertaken with a team of porters and biologist George Schaller (GS). Ostensibly a scientific expedition to observe the elusive snow leopard, the journey evolves into a spiritual quest, catalyzed by the narrator’s grief over his wife’s death. This study engaged with the framework of travel narrative to explore how physical movement serves as a means of psychological release and spiritual transformation. It employed a qualitative textual analysis approach, emphasizing themes of travel to nature and spiritual transcendence critical theory developed by Michael Cronin and R.W. Emerson. Both of them take travel and nature as the transcendental means for the spiritual awakening. In the novel, the narrator undergoes an internal metamorphosis as the travelers navigate the snow-laden mountains, interact with the region’s people, and encounter Hindu and Buddhist sacred spaces. The wilderness becomes a medium for detachment from personal sorrow and worldly desires, guiding him toward transcendental peace. The novel ultimately exemplifies a journey from the known to the unknown, the physical to the spiritual, and personal suffering to profound enlightenment.